Characterization of chronic arthritis in a multicenter study of 852 childhood-onset systemic lupus erythematosus patients - Sakamoto, Ana Paula; Silva, Clovis Artur; Ferriani, Mariana Paes Leme; Pereira, Rosa Maria Rodrigues; Bonfá, Eloisa; Saad-Magalhães, Claudia [UNESP]; Okuda, Eunice; Appenzeller, Simone; Gomes, Francisco Hugo; Cunha, Ana Luiza Garcia; Salume, Mirna Henriques Tomich; Piotto, Daniela Petry; et al. (Springer Nature, 2016)
Chronic arthritis (CA) is an unusual condition in childhood-onset systemic lupus erythematosus (cSLE) and data in children is very limited. The aim of the study is to assess CA in a large population of cSLE patients, in a multicenter cross-sectional study including 852 cSLE patients followed in ten Pediatric Rheumatology referral services in state of São Paulo, Brazil. CA was observed in 32/852 (3.7 %) cSLE patients mostly in hands and ankles. Chronic monoarthritis was diagnosed in four cSLE patients, oligoarthritis in nine and polyarthritis in 19. In the latter group, six had rhupus syndrome. Two oligoarticular patients had Jaccoud’s arthropathy. CA was an isolated manifestation observed at disease onset in 13/32 (41 %) cSLE patients, and juvenile idiopathic arthritis (JIA) was the first diagnosis in 18/32 (56 %). The comparison of last visit of patients with CA and without this manifestation revealed higher frequency of splenomegaly (28 vs. 11 %, p = 0.002). The median of SLICC/ACR-DI score [1(0–9) vs. 0(0–7), p = 0.003] was significantly higher in CA patients compared to patients without this manifestation, likewise the frequency of musculoskeletal damage (31 vs. 9 % p = 0.001). Frequencies of treatment with nonsteroidal anti-inflammatory drugs (75 vs. 26 %, p < 0.0001), hydroxychloroquine sulfate (87 vs. 59 %, p = 0.001) and methotrexate (47 vs. 22 %, p = 0.001) were significantly higher in CA patients. This large multicenter study allowed us to characterize CA as a rare and early manifestation of cSLE, frequently mimicking JIA at disease onset. It is predominantly polyarticular, involving more often hands and ankles and it is associated with significant musculoskeletal accrual damage.
Keywords: Childhood; Childhood-onset systemic lupus erythematosus; Chronic arthritis; Jaccoud’s arthropathy; Rhupus; Systemic lupus erythematosus